2016
DOI: 10.1186/s12885-016-2736-9
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib added to FOLFIRI versus FOLFIRI in patients with chemorefractory advanced adenocarcinoma of the stomach or lower esophagus: a randomized, placebo-controlled phase II AIO trial with serum biomarker program

Abstract: BackgroundAs a multi-targeted anti-angiogenic receptor tyrosine kinase (RTK) inhibitor sunitinib (SUN) has been established for renal cancer and gastrointestinal stromal tumors. In advanced refractory esophagogastric cancer patients, monotherapy with SUN was associated with good tolerability but limited tumor response.MethodsThis double-blind, placebo-controlled, multicenter, phase II clinical trial was conducted to evaluate the efficacy, safety and tolerability of SUN as an adjunct to second and third-line FO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 46 publications
2
67
1
Order By: Relevance
“…The trial explored the additional benefit of sunitinib to standard of care on PFS or OS and did not meet the primary endpoint. 10 However, we did observe a significant reduction of M30 and M65 during therapy independently of tumor load. Again, the multi-tyrosine kinase inhibitor sunitinib did not have an added effect on M30 or M65 reduction.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The trial explored the additional benefit of sunitinib to standard of care on PFS or OS and did not meet the primary endpoint. 10 However, we did observe a significant reduction of M30 and M65 during therapy independently of tumor load. Again, the multi-tyrosine kinase inhibitor sunitinib did not have an added effect on M30 or M65 reduction.…”
Section: Discussioncontrasting
confidence: 48%
“…Importantly, the clinical characteristic of this subgroup did not differ from the entire cohort. 10 In summary, the current analysis suggests that M30 and M65 in the serum of patients with advanced gastric cancer undergoing palliative chemotherapy could be used as a predictive biomarker for treatment response. Also, a correlation with disease location and the presence of metastasis was established.…”
Section: Discussionmentioning
confidence: 84%
“…The authors furthermore identified higher baseline VEGFC serum levels in sunitinib responders. With sunitinib monotherapy only showing modest efficacy, sunitinib was next tested in addition to the FOLFIRI chemotherapy scheme as second-or third-line treatment for advanced adenocarcinoma of the stomach or lower esophagus (Moehler et al, 2016). Here, a similar median PFS between both groups and a trend towards prolonged median OS in the FOLFIRI/Sunitinib group was found.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, stomatitis, diarrhea and hand–foot syndrome were significantly more frequent in the combination treatment arm than in the docetaxel arm. The second trial, conducted in Germany, included FOLFIRI with or without sunitinib as the second‐ or third‐line treatment . This study did not demonstrate any benefit with sunitinib plus FOLFIRI compared with FOLFIRI in any of the efficacy markers.…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 92%